Health Literacy Based Health Promotion Strategy for the Prevention of Periodontal Disease Caused by Porphyromonas gingivalis in Communities Exposed to Environmental Heavy Metals: A Scoping Review - Helena Jelita; Harun Achmad; Syamsul Ariifn; Ira Jayanti; Hanasia Hanasia; Firdaus Hamid (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Periodontal disease in communities exposed to environmental heavy metals represents not only a biological problem but also a public health challenge closely linked to limitations in health literacy. While the pathogenic role of Porphyromonas gingivalis and the toxic effects of heavy metals such as Pb, Cd, and Hg contribute to inflammation and periodontal tissue damage, insufficient health literacy constrains individuals’ capacity to recognize risks, adopt preventive behaviors, and engage in effective disease prevention strategies. Methods: A scoping review was conducted using the PEOS framework, with article searches in PubMed, ScienceDirect, EBSCO, and Google Scholar. Of the 512 articles identified, 20 met the inclusion criteria (2015–2023) and were analyzed through data charting and quality assessment. Results: Heavy metals have been shown to increase the risk of periodontitis through immune suppression, oxidative stress, and changes in the oral microbiota. P. gingivalis enhances pathogenesis by disrupting epithelial defenses and triggering chronic inflammation. Increasing health literacy has been shown to be influential in encouraging preventative behaviors and managing environmental exposure risks. Conclusion: Strengthening health literacy is a central and unifying strategy in reducing periodontal disease risk in populations exposed to environmental heavy metals. Integrating biologically informed risk communication with community-based, literacy-sensitive health promotion interventions enhances prevention efforts against periodontal disease associated with P. gingivalis in high-risk communities